3. KEGAGALAN DIPLOMASI PEMERINTAH AUSTRALIA DALAM PEMBEBASAN TERPIDANA HUKUMAN MATI KASUS BALI NINE DI INDONESIA - Yulia Alfeini; Hermini Susiatiningsih; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Execution of the death penalty in The Bali Nine Case made The Government of Australiadid some of diplomatic efforts to rescue the two Australian prisoners, namely MyuranSukumaran and Andrew Chan. Those efforts are made through smart diplomacy, the typeof diplomacy that combines soft power diplomacy and hard power diplomacy. Moreover,there were also diplomatic efforts that undertaken by the international organization torescue both of convicted from the death penalty. However, the entire diplomacy was failedafter the decisions to reject the clemency for the two prisoners was issued by ThePresident Jokowi, which in turn made the bilateral relation between Indonesia andAustralia were in conflict. This research aim to analyze the cause of releasing thedecisions to reject the clemency in The Bali Nine case, which is also causing the failure ofAustralian Government’s diplomacy to Indonesia in that case. The framework used in thisresearch is the concept of diplomacy and foreign policy to explain the case of Bali Nine,and also the theory of foreign policy analysis by Snyder to analyze the decisions in therejection of clemency. The type of this research is explanatory, using qualitative dataanalysis techniques from the primary and secondary data accumulation. The result of thisresearch explains that there are four determinant factors that come from the internal andexternal state, which makes the rejection of clemency decision (Indonesia). These fourfactors include: The first factor comes from the perspective of President Jokowi and hisgovernment as the main actor of policymakers for the rejection of clemency. The secondcomes from the public opinion of Indonesian people through the case of Bali Nine. Thethird comes from the relation between Indonesia and Australia in Tony Abbott’s era, whilethe fourth comes from the perception of the countries in Southeast Asia against drugscrime.